A method for detecting the quality of a patch replacing the colorectal seromuscular layer
By using polylactic acid-polycaprolactone copolymer solution, and micropore technology and quality testing, the problem of insufficient biocompatibility and functionality of patch materials in the prior art is solved, and higher safety and effectiveness are achieved.
Patent Information
- Application Number
- CN202411026921.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The colorectal sarcoplasmic patch materials in the prior art have limitations in terms of biocompatibility and functionality, which may cause mismatch in immune rejection reactions and material degradation rates, resulting in the occurrence of postoperative complications and adverse events.
The polylactic acid-polycaprolactone copolymer solution is used as the patch material, and the patch is prepared through micropore technology, heat treatment and cooling treatment, and quality testing is carried out, including the analysis of micropore characterization values, performance characterization values and degradation characterization values to determine whether the patch is qualified.
Through strict quality testing, ensure the safety, effectiveness and compliance of the patch, reduce the risk of postoperative adverse reactions, improve the biocompatibility and functionality of the patch, and ensure that it can play the expected role after implantation.
Smart Images

Figure CN118961534B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical technology, and in particular to a method for detecting the quality of a patch replacing the seromuscular layer of the colorectum. Background Art
[0002] The colorectal seromuscular layer is the innermost layer of the colorectal wall, located between the submucosal layer and the muscular layer. This layer is composed of connective tissue and smooth muscle, and mainly serves to connect the inner wall and the outer wall. In the colorectal seromuscular layer, the composition and structure of the connective tissue will be different, which is closely related to its function. The arrangement of smooth muscle fibers will also vary depending on their location. For example, in the circular muscle of the intestine, the smooth muscle fibers are arranged in a circular shape, while in the longitudinal muscle of the intestine, the smooth muscle fibers are arranged in a longitudinal shape. The function of the colorectal seromuscular layer is mainly to control the peristalsis and emptying of the intestine, and it also plays a certain role in the digestion and absorption of the intestine. In addition, the colorectal seromuscular layer also interacts with the intestinal immune system to help resist the invasion of pathogens and foreign substances. When the colorectal seromuscular layer is damaged or affected by disease, inflammation, infection, ulcers and other problems may occur, leading to impaired intestinal function. Therefore, maintaining the health of the colorectal seromuscular layer is very important for maintaining the overall health of the intestine.
[0003] China Publication No. CN101773689B discloses a tissue repair patch, which has a hyaluronic acid film or a hyaluronic acid and collagen mixture film on the surface of a polymer surgical biological patch. The material of the polymer surgical biological patch is a synthetic polymer material, and the polymer surgical biological patch can be made by electrostatic spinning or monofilament spinning. Publication No. CN116407679A discloses a large-size porous myocardial patch and a preparation method thereof. The large-size porous myocardial patch prepared by the patch has good process stability of size, is not easy to shrink and deform, has stable mechanical properties, and shortens the production cycle from several days to several hours; the internal porosity is as high as 91%. Compared with the non-perforated patch, the laser-perforated patch is more conducive to the migration and growth of cells into the patch, so it is conducive to promoting angiogenesis on the patch and repairing heart function in clinical application.
[0004] However, the colorectal seromuscular layer patch materials in the existing technology have certain limitations in biocompatibility and functionality, and may cause problems such as immune rejection reactions and mismatched material degradation rates, which may lead to postoperative complications and adverse events and cause harm to the patient's body. Therefore, a method for detecting the quality of the patch is needed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for detecting the quality of a patch that replaces the colorectal seromuscular layer, so as to solve the technical problems in the above background.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for detecting the quality of a patch replacing the colorectal seromuscular layer, comprising:
[0008] Step 1: preparing a patch material, the patch material comprising: a polylactic acid-polycaprolactone copolymer solution;
[0009] Step 2: Pour the patch material into the mold and perform microporous technology treatment;
[0010] Step 3: heat treatment and cooling treatment;
[0011] Step 4: sampling the obtained patch, performing quality inspection on the sample, obtaining the sample parameter characterization value, and performing comparative analysis on the sample parameter characterization value to determine whether the patch is qualified;
[0012] The sample parameter characterization value threshold is preset to be, and the sample parameter characterization value is compared and analyzed with the sample parameter characterization value threshold;
[0013] If the sample parameter characterization value is less than the sample parameter characterization value threshold, the patch is judged to be qualified;
[0014] If the sample parameter characterization value ≥ the sample parameter characterization value threshold, the patch is judged to be unqualified.
[0015] As a further solution of the present invention: the specific method for performing quality detection on the sample is:
[0016] A1: Obtain the test data of the patch sample;
[0017] The test data include: micropore characterization value, performance characterization value, and degradation characterization value;
[0018] A2: Obtain sample parameter characterization values based on the test data of the patch sample;
[0019] A3: Compare and analyze the sample parameter characterization values to determine whether the patch is qualified.
[0020] As a further solution of the present invention: the method for obtaining the micropore characterization value is:
[0021] C1: Setting a photosensitive element and attaching the photosensitive element to one side of the patch sample, and exposing the other side of the patch sample to obtain a pattern with only shadow areas and bright areas;
[0022] C2: According to the obtained pattern, the diameter of each bright area is measured, and the average is calculated to obtain the average diameter. The ratio of the average diameter to the average diameter threshold is the aperture characterization value, and the aperture characterization value is marked as R;
[0023] C3: According to the obtained pattern, the distance between the centers of each bright area is measured, and the average is calculated to obtain the average distance. The ratio of the average distance to the average distance threshold is the pore characterization value, and the pore characterization value is marked as L;
[0024] C4: Process the pore size characterization value R and the pore characterization value L, using the formula: The micropore characterization value K is calculated, where a 1 , a 2 are preset proportional coefficients, and are all greater than 0.
[0025] As a further solution of the present invention: the method for obtaining the performance characterization value is:
[0026] D1: Take a part of the patch sample to perform tensile strength test to obtain the tensile strength characterization value;
[0027] D2: Take a part of the patch sample to perform bending strength test to obtain the bending strength characterization value;
[0028] D3: Calculate the performance characterization value based on the tensile strength characterization value and the bending strength characterization value.
[0029] As a further solution of the present invention: the method for obtaining the degradation characterization value is:
[0030] E1: The remaining patch samples were subjected to in vitro degradation experiments;
[0031] E2: Record the time taken for degradation. The ratio of the time taken for degradation to the threshold of the time taken for degradation is the degradation time characterization value, and the degradation time characterization value is marked as T;
[0032] E3: Analyze the degradation products produced after the degradation experiment to determine whether the degradation products are toxic, and digitally process the degradation products according to whether the degradation products are toxic, and mark the degradation products as J, such as marking toxic degradation products as 1 and non-toxic degradation products as 0;
[0033] E4: Calculate the degradation characterization value W based on the degradation time characterization value T and the degradation product J;
[0034] The degradation time characterization value T and the degradation product J are processed by the formula: W = c 1 ×T+c 2 ×J, calculate the degradation characterization value W, where c 1 , c 2 are preset weight coefficients, and are all greater than 0.
[0035] As a further solution of the present invention: the method for obtaining the sample parameter characterization value is:
[0036] The micropore characterization value K, performance characterization value N and degradation characterization value W are processed by the formula: Calculate the sample parameter characterization value Y, where d 1 , d 2 , d 3 are preset scaling factors, and are all greater than 0.
[0037] As a further solution of the present invention: the sample parameter characterization value threshold is preset as YL, and the sample parameter characterization value Y is compared and analyzed with the sample parameter characterization value threshold YL;
[0038] If Y<YL, the patch is considered qualified and can be put into use;
[0039] If Y≥YL, the patch is judged to be unqualified and cannot be put into use.
[0040] As a further solution of the present invention: the method for obtaining the tensile strength characterization value is:
[0041] The length of the obtained patch sample is measured, and the patch sample is stretched. The length of the patch sample when the patch sample is broken is measured, and the difference is calculated with the length of the patch sample when it is not stretched to obtain the stretched length. The ratio of the stretched length to the stretch length threshold is the tensile strength characterization value, and the tensile strength characterization value is marked as Q.
[0042] As a further solution of the present invention: the method for obtaining the bending strength characterization value is:
[0043] The obtained patch sample is folded and bent in half, and the bending angle of the patch sample when the patch sample breaks during the folding and bending process is recorded. The ratio of the bending angle to the angle threshold is the bending strength characterization value, and the bending strength characterization value is marked as P.
[0044] As a further solution of the present invention: the method for obtaining the performance characterization value is:
[0045] The tensile strength characterization value Q and the bending strength characterization value P are processed by the formula: Calculate the performance characterization value N, where b 1 , b 2 are preset ratio parameters, and are all greater than 0.
[0046] Beneficial effects of the present invention:
[0047] The present invention ensures the safety, effectiveness, compliance and improvement of medical quality of the patch by judging whether the patch is qualified. Through strict quality inspection, it can ensure that the patch material used will not cause adverse reactions such as inflammation and infection, thereby reducing surgical risks, ensuring that the patch can play an expected role after implantation and improving the surgical effect. It can ensure that the patch material used has excellent performance and quality, thereby improving the quality and effect of the operation and providing better medical services to patients. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The present invention will be further described below in conjunction with the accompanying drawings.
[0049] Figure 1 It is a flow chart of the steps of the present invention;
[0050] Figure 2 is a flow chart of judging whether a patch is qualified according to the present invention;
[0051] Figure 3 It is a flow chart of calculating the sample parameter characterization value of the present invention. DETAILED DESCRIPTION
[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] See also Figure 1 - Figure 3 As shown, the present invention is a method for detecting the quality of a patch replacing the colorectal seromuscular layer, comprising:
[0054] Step 1: preparing a patch material, the patch material comprising: a polylactic acid-polycaprolactone copolymer solution;
[0055] The polylactic acid and polycaprolactone are mixed in a mass ratio of 1:1, a solvent is added to the mixture, and the mixture is stirred until the polymer is completely dissolved to obtain a copolymer solution;
[0056] Step 2: Pour the patch material into the mold and perform microporous technology treatment;
[0057] The copolymer solution is evenly poured into the mold of the bionic structure to ensure that the material is flat and free of bubbles, and the patch material in the mold is processed with micropores. After the processing is completed, the patch is taken out from the mold to obtain the initial patch mold;
[0058] Micro hole processing includes: mechanical processing, EDM processing, laser processing;
[0059] Step 3: heat treatment and cooling treatment;
[0060] The patch mold is heat treated at 120°C for 30 minutes to set the material;
[0061] The heat-treated patch is cooled at room temperature for 30 minutes to cool the material to room temperature;
[0062] Step 4: sampling the obtained patch, performing quality inspection on the sample, obtaining the sample parameter characterization value, and performing comparative analysis on the sample parameter characterization value to determine whether the patch is qualified;
[0063] A1: Obtain the test data of the patch sample;
[0064] The test data include: micropore characterization value, performance characterization value, and degradation characterization value;
[0065] It should be noted that parameters such as pore size and porosity reflect the material's air permeability, cell growth and material exchange capabilities. The ideal pore size and pore range should be conducive to cell growth and material exchange, while preventing tissue from growing into the pores.
[0066] Mechanical property testing can evaluate the mechanical strength and stability of the patch when subjected to physiological stress and strain, which helps to ensure that the patch can withstand normal physiological loads after implantation and work together with surrounding tissues;
[0067] Biodegradation performance testing can evaluate the degradation rate and degradation products of the patch in the body. An ideal biodegradable material should be completely degraded within a certain period of time, and the degradation products should be non-toxic and harmless and be excreted from the body through normal physiological pathways, which helps ensure that the patch can be gradually absorbed or excreted by the body after completing its function, reducing the risk of long-term retention.
[0068] In summary, these test indicators reflect the quality of the patch from different aspects, including air permeability, mechanical properties, cell growth and material exchange capacity, as well as biocompatibility and safety. Through these tests, the quality and performance of the patch can be comprehensively evaluated to ensure that it meets the requirements of clinical application.
[0069] B1: Obtain the micropore characterization value of the patch sample;
[0070] C1: Setting a photosensitive element and attaching the photosensitive element to one side of the patch sample, and exposing the other side of the patch sample to obtain a pattern with only shadow areas and bright areas;
[0071] C2: According to the obtained pattern, the diameter of each bright area is measured, and the average is calculated to obtain the average diameter. The ratio of the average diameter to the average diameter threshold is the aperture characterization value, and the aperture characterization value is marked as R;
[0072] C3: According to the obtained pattern, the distance between the centers of each bright area is measured, and the average is calculated to obtain the average distance. The ratio of the average distance to the average distance threshold is the pore characterization value, and the pore characterization value is marked as L;
[0073] C4: Process the pore size characterization value R and the pore characterization value L, using the formula: The micropore characterization value K is calculated, where a 1 , a 2 are preset proportional coefficients, and are all greater than 0;
[0074] B2: Obtain performance characterization values of patch samples;
[0075] D1: Take a part of the patch sample for tensile strength test;
[0076] The length of the obtained patch sample is measured, and the patch sample is stretched. The length of the patch sample when the patch sample is broken is measured, and the difference between the length of the patch sample when it is not stretched is calculated to obtain the stretched length. The ratio of the stretched length to the stretched length threshold is the tensile strength characterization value, and the tensile strength characterization value is marked as Q;
[0077] D2: Take a part of the patch sample for bending strength test;
[0078] The obtained patch sample is folded and bent in half, and the bending angle of the patch sample when the patch sample breaks during the folding and bending process is recorded. The ratio of the bending angle to the angle threshold is the bending strength characterization value, and the bending strength characterization value is marked as P;
[0079] D3: Calculate the performance characterization value based on the tensile strength characterization value Q and the bending strength characterization value P;
[0080] The tensile strength characterization value Q and the bending strength characterization value P are processed by the formula: Calculate the performance characterization value N, where b 1 , b 2 are preset ratio parameters, and are all greater than 0;
[0081] B3: Obtain the degradation characterization value of the patch sample;
[0082] E1: The remaining patch samples were subjected to in vitro degradation experiments;
[0083] E2: Record the time taken for degradation. The ratio of the time taken for degradation to the threshold of the time taken for degradation is the degradation time characterization value, and the degradation time characterization value is marked as T;
[0084] E3: Analyze the degradation products produced after the degradation experiment to determine whether the degradation products are toxic, and digitally process the degradation products according to whether the degradation products are toxic, and mark the degradation products as J, such as marking toxic degradation products as 1 and non-toxic degradation products as 0;
[0085] E4: Calculate the degradation characterization value W based on the degradation time characterization value T and the degradation product J;
[0086] The degradation time characterization value T and the degradation product J are processed by the formula: W = c 1 ×T+c 2 ×J, calculate the degradation characterization value W, where c 1 , c 2 are preset weight coefficients, and are all greater than 0;
[0087] A2: Obtain sample parameter characterization values based on the test data of the patch sample;
[0088] The micropore characterization value K, performance characterization value N and degradation characterization value W are processed by the formula: Calculate the sample parameter characterization value Y, where d 1 , d 2 , d 3 are preset scaling factors, and are all greater than 0;
[0089] A3: Compare and analyze the sample parameter characterization values to determine whether the patch is qualified;
[0090] The sample parameter characterization value threshold is preset as YL, and the sample parameter characterization value Y is compared and analyzed with the sample parameter characterization value threshold YL;
[0091] If Y<YL, the patch is considered qualified and can be put into use;
[0092] If Y≥YL, the patch is deemed unqualified and cannot be put into use;
[0093] The working principle of the present invention is as follows: Step 1: Prepare patch material, the patch material includes: polylactic acid-polycaprolactone copolymer solution; Step 2: Pour the patch material into a mold and perform microporous technology treatment; Step 3: Perform heat treatment and cooling treatment; Step 4: Sampling the obtained patch, performing quality inspection on the sample, and obtaining the sample parameter characterization value, and performing comparative analysis on the sample parameter characterization value to determine whether the patch is qualified; the sample parameter characterization value threshold is preset, and the sample parameter characterization value is compared and analyzed with the sample parameter characterization value threshold; if the sample parameter characterization value is less than the sample parameter characterization value threshold, the patch is determined to be qualified; if the sample parameter characterization value is greater than or equal to the sample parameter characterization value threshold, the patch is determined to be unqualified.
[0094] The above thresholds are set for the convenience of comparison. The thresholds depend on the amount of sample data and the number of bases set by technicians in this field for each set of sample data.
[0095] The above formulas are obtained by collecting a large amount of data and performing software simulation to select a formula close to the actual value. The factors in the formula are set by technicians in this field according to actual conditions; for example: Formula A technician in this field collects multiple groups of test data and sets corresponding sample parameter characterization values for each group of test data; substitutes the set sample parameter characterization values and the collected test data into the formula, any three formulas constitute a three-variable linear equation system, and the calculated factors are screened and averaged to obtain d 1 , d 2 and 3 The values of are 2.47, 1.65 and 3.23 respectively;
[0096] The size of the factor is to quantify each parameter to obtain a specific value for subsequent comparison. The size of the factor depends on the amount of test data and the preliminary setting of the corresponding sample parameter characterization value for each set of test data by technicians in this field; as long as it does not affect the proportional relationship between the parameter and the quantified value, such as the sample parameter characterization value is proportional to the degradation characterization value. An embodiment of the present invention is described in detail above, but the content described is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equal changes and improvements made within the scope of application of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for detecting the quality of a patch replacing the colorectal seromuscular layer, characterized in that: include: Step 1: preparing a patch material, the patch material comprising: a polylactic acid-polycaprolactone copolymer solution; Step 2: Pour the patch material into the mold and perform microporous technology treatment; Step 3: heat treatment and cooling treatment; Step 4: sampling the obtained patch, performing quality inspection on the sample, obtaining the sample parameter characterization value, and performing comparative analysis on the sample parameter characterization value to determine whether the patch is qualified; Preset a sample parameter characterization value threshold, and compare and analyze the sample parameter characterization value with the sample parameter characterization value threshold; If the sample parameter characterization value is less than the sample parameter characterization value threshold, the patch is judged to be qualified; If the sample parameter characterization value is ≥ the sample parameter characterization value threshold, the patch is judged to be unqualified; The specific method for quality testing of samples is as follows: A1: Obtain the test data of the patch sample; The test data include: micropore characterization value, performance characterization value, and degradation characterization value; A2: Obtain sample parameter characterization values based on the test data of the patch sample; A3: Compare and analyze the sample parameter characterization values to determine whether the patch is qualified; The method for obtaining the sample parameter characterization value is: The micropore characterization value, performance characterization value and degradation characterization value are processed to obtain the sample parameter characterization value Y by calculation; The sample parameter characterization value threshold is preset as YL, and the sample parameter characterization value Y is compared and analyzed with the sample parameter characterization value threshold YL; If Y<YL, the patch is considered qualified and can be put into use; If Y≥YL, the patch is deemed unqualified and cannot be put into use; The pore size characterization value and the pore characterization value are processed to obtain the micropore characterization value by calculation; The method for obtaining the performance characterization value is: Taking a portion of the patch sample for tensile strength testing to obtain a tensile strength characterization value; Taking a portion of the patch sample to perform a bending strength test to obtain a bending strength characterization value; Wherein, the performance characterization value is calculated based on the tensile strength characterization value and the bending strength characterization value; According to the degradation time characterization value and the degradation product, the degradation time characterization value and the degradation product are subjected to data processing to calculate the degradation characterization value; Wherein, a photosensitive element is provided and attached to one side of the patch sample, and exposure is performed on the other side of the patch sample, so as to obtain a pattern with only shadow areas and bright areas; according to the obtained pattern, the diameter of each bright area is measured, and the mean is calculated to obtain the average diameter, and the ratio of the average diameter to the average diameter threshold is the aperture characterization value; according to the obtained pattern, the distance between the centers of each bright area is measured, and the mean is calculated to obtain the average distance, and the ratio of the average distance to the average distance threshold is the pore characterization value; Among them, the remaining patch samples are subjected to in vitro degradation experiments; the time taken for degradation is recorded, and the ratio of the time taken for degradation to the threshold time taken for degradation is the degradation time characterization value; Analyze the degradation products produced after the degradation experiment to determine whether the degradation products are toxic, and digitally process the degradation products based on whether the degradation products are toxic; The length of the obtained patch sample is measured, and the patch sample is stretched. The length of the patch sample when the patch sample is broken is measured, and the difference between the length of the patch sample when it is not stretched is calculated to obtain the stretched length. The ratio of the stretched length to the stretched length threshold is the tensile strength characterization value. The obtained patch sample is folded and bent in half, and the bending angle of the patch sample when the patch sample breaks during the folding and bending process is recorded. The ratio of the bending angle to the angle threshold is the bending strength characterization value.
2. A method for detecting the quality of a patch for replacing the colorectal seromuscular layer according to claim 1, characterized in that: The method for obtaining the performance characterization value is: The tensile strength characterization value Q and the bending strength characterization value P are processed by the formula: , calculate and obtain the performance characterization value N, where, , are preset ratio parameters, and are all greater than 0.
Citation Information
Patent Citations
Surgical repairing patch
CN101773689B
Large-size porous myocardial patch as well as preparation method and application thereof
CN116407679A